Microbiological Hazard Identification and Exposure Assessment of Poultry Products Sold in Various Localities of Hyderabad, India - Rao V. Sudershan; R. Naveen Kumar; L. Kashinath; V. Bhaskar; K. Polasa (The Scientific World Journal)
A study was carried out to identify microbiological hazards and assess their exposure associated with consumption of poultry based street food served in different localities of Hyderabad. The study indicated that chicken 65, chicken fried rice, chicken noodles, chicken Manchuria and chilly chicken are the most common recipes. A process flow diagram was developed to identify critical control points in the food item. After analysis of the samples at each level of preparation, it was observed that rice and noodles were kept at room temperature for about 5-6 hrs which was a critical control point. A total of 376 samples including chicken fried rice, chicken noodles, boiled noodles and boiled rice were collected from circle 1, 2, 3, 4, 5, 6, and 7 of Greater Hyderabad municipal corporation (GHMC) and analyzed for microbiological examination. The most prevalent pathogenic bacteria isolated were S. aureus (3.4 log 10 cfu/g) and B. cereus (3.4 log 10 cfu/g). Salmonella spp. was present in salads (3.2 log 10 cfu/g) and hand washings of the food handler (3.5 log 10 cfu/g). Salmonella contamination was found in salads served along with chicken fried rice and chicken noodles than in the food.